2020
DOI: 10.1097/md.0000000000018610
|View full text |Cite
|
Sign up to set email alerts
|

Stretta procedure versus proton pump inhibitors for the treatment of nonerosive reflux disease

Abstract: To compare the Stretta procedure with proton pump inhibitors for the treatment of nonerosive reflux disease (NERD). From July 2018 to April 2019, patients diagnosed with NERD and referred for treatment were enrolled. They were treated with either Stretta procedure or proton pump inhibitor (PPI) medication and followed-up for 6 months. The symptom control, quality of life, lower esophageal sphincter (LES) pressure, 24-hour pH parameters, PPI usage and satisfaction rate were evaluated. The complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Also in the study of He et al [ 5 ], the symptom score improvement was significantly higher in the STRETTA group of 26 patients compared with the PPI group of 21 patients after 6 mo, whereas both interventions improved, without significant differences, the 24 h pH parameters, including the number of acid episodes, acid exposure time, and DeMeester score.…”
Section: To the Editormentioning
confidence: 90%
“…Also in the study of He et al [ 5 ], the symptom score improvement was significantly higher in the STRETTA group of 26 patients compared with the PPI group of 21 patients after 6 mo, whereas both interventions improved, without significant differences, the 24 h pH parameters, including the number of acid episodes, acid exposure time, and DeMeester score.…”
Section: To the Editormentioning
confidence: 90%
“…SRF (13): first, upper gastrointestinal endoscopy was performed to confirm the location and depth of the squamocolumnar junction (SCJ). The endoscope was then removed, and the Stretta catheter was positioned 1 cm above the SCJ according to the distance previously determined.…”
Section: Treatment and Proceduresmentioning
confidence: 99%
“…Moreover, data demonstrated that it carries more adverse events like dysphagia, abdominal distension, diarrhea, chronic stomach pain and recurrence of GERD when compared to other endoscopic approaches. However, when compared to PPI use alone, it shows superior outcomes 37…”
Section: Endoscopic Alternativesmentioning
confidence: 99%